Type 2 Diabetes and Aging: A Not so Sweet Scenario for Bone - Dhaliwal, R.; Rosen, C. J. (Hormone and Metabolic Research, 2016)
Type 2 diabetes and fractures are associated with substantial mortality and morbidity in the aging population. Given the normal to high bone mineral density, skeletal fragility in type 2 diabetes is an intriguing topic of ongoing research. An improved understanding of the underlying mechanisms and regulators of bone pathology in diabetes is needed to formulate targeted prevention and intervention strategies in this high risk population. Although the changes in bone induced by aging and disease are divergent, the pathogenetic mechanisms of aging and type 2 diabetes, thus far known, are not mutually exclusive. These mechanisms may provide deeper insight into the quantitative and qualitative deficits to further our knowledge of diabetes-specific bone pathology.
Keywords: diabetes mellitus; aging; bone quality; osteoporosis; senescence; advanced glycation end products